The Application of the Dualistic Doctrine at the Investigation Stage under the 2025 Criminal Procedure Code - Undang Prasetya Umara; Nanda Saputra Umara (Jurnal Hukum Replik, 2026)
This article examines the application of the dualistic doctrine at the investigation stage under the 2025 Criminal Procedure Code and its implications for legal certainty and the protection of suspects’ rights within Indonesia’s criminal justice system. The dualistic doctrine, which emphasizes a clear separation between the criminal act and criminal liability, is analyzed as a theoretical framework that should guide investigators’ authority in determining suspect status and employing coercive measures. This study employs normative legal research with empirical reinforcement, using statutory, conceptual, and case approaches, complemented by an analysis of investigative practices and the pretrial mechanism. The findings demonstrate that although the 2025 Criminal Procedure Code has normatively accommodated the principles of the dualistic doctrine and due process of law, its implementation in investigative practice remains inconsistent, as reflected in the tendency toward premature designation of suspects and the disproportionate use of coercive measures. Such disregard for the dualistic doctrine results in weakened legal certainty, erosion of the presumption of innocence, and the emergence of legal suffering and social stigmatization for suspects, even in cases that ultimately do not lead to criminal conviction. This article argues that the dualistic doctrine is not only relevant as a doctrine of substantive criminal law, but also serves a strategic function in criminal procedural law as an operational principle that limits investigative power, strengthens the role of pretrial review, and preserves the legitimacy of the criminal justice system. Accordingly, the consistent internalization of the dualistic doctrine at the investigation stage under the 2025 Criminal Procedure Code constitutes an essential prerequisite for the realization of a fair criminal justice system that ensures legal certainty and is oriented toward the protection of human rights.KeywordsDualistic doctrine, investigation, Criminal Procedure Code 2025, suspect determination, criminal procedure law.